Tinjauan Minat Beli Siswa Jurusan Tata Kecantikan Rambut SMK N 7 Padang Terhadap Produk Kosmetik Pemutih Wajah - Sa'diah, Halimatun; Rostamailis, Rostamailis; Yanita, Merita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
This research is motivated by so many things that make consumers interested to buy a cosmetic product, one of them is to buy a facial whitening cosmetics. Based on the purpose of this study was to determine buying interest of the facial whitening cosmetics by the students in Hairstyling Department of SMK Negeri 7.This type of research is quantitative descriptive. The population in this study was students in grade XII, which consists of two classes, namely class XII Beauty 1 and XII Beauty 2 Hairstyling Department of SMK Negeri 7 Padang which amounts to 36 students and all of the population used as a sample (total sampling). A data collection technique is to use a questionnaire, which has been tested for validity and reliability. Data were analyzed using the Achievement Level Percentage of Respondents (TPR).The results showed that the percentage of respondents’ level of achievement on the indicator products (78%) with the Medium category, the percentage of respondents’ level of achievement on the indicator price (80%) with the High category. While the percentage of respondents’ achievement on the indicator promotion (80%) with High category. For the percentage of respondents’ to the achievement of students' interest in buying facial whitening cosmetics (79%) with the Medium category. It is suggested to students and other consumers into buying facial whitening cosmetics are not only based on price and promotions, but rather the product itself.Keywords : Interest But, Product, Price, Promotion